2014
DOI: 10.1080/17290376.2014.890123
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a bar-based sexual risk reduction intervention for bar patrons in Tshwane, South Africa

Abstract: Alcohol consumption is a recognised risk factor for HIV infection. Alcohol serving establishments have been identified as appropriate venues in which to deliver HIV prevention interventions. This paper describes experiences and lessons learnt from implementing a combined HIV prevention intervention in bar settings in one city- and one township-based bar in Tshwane, South Africa. The intervention consisted of peer-led and brief intervention counselling sub-components. Thirty-nine bar patrons were recruited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A more recent systematic review of adherence-enhancing interventions for ART in sub-Saharan Africa identified MI for alcohol-dependent patients as the only one of 21 identified strategies to find a significant impact on adherence [ 49 ]. A recent study in South Africa also showed that it was feasible to implement a combined alcohol and HIV prevention intervention in bar settings, consisting of peer-led brief interventions based on MI, delivered to bar patrons [ 50 ]. Another recent systematic review of interventions to reduce HIV transmission in the context of sex work also highlighted the need to develop and evaluate effective alcohol-control strategies [ 51 ], and notably, of the 26 intervention studies identified among female sex workers in sub-Saharan Africa only one was aimed at the adoption of safer drinking patterns [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A more recent systematic review of adherence-enhancing interventions for ART in sub-Saharan Africa identified MI for alcohol-dependent patients as the only one of 21 identified strategies to find a significant impact on adherence [ 49 ]. A recent study in South Africa also showed that it was feasible to implement a combined alcohol and HIV prevention intervention in bar settings, consisting of peer-led brief interventions based on MI, delivered to bar patrons [ 50 ]. Another recent systematic review of interventions to reduce HIV transmission in the context of sex work also highlighted the need to develop and evaluate effective alcohol-control strategies [ 51 ], and notably, of the 26 intervention studies identified among female sex workers in sub-Saharan Africa only one was aimed at the adoption of safer drinking patterns [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morojele and colleagues also conducted a multilevel intervention in alcohol venues in South Africa (88). In this study, the researchers implemented a multilevel intervention in two licensed drinking establishments, one in a city and one in a township in Gauteng province.…”
Section: What Interventions Have Been Based In Alcohol-venues?mentioning
confidence: 99%
“…Eighteen percent (18%) of youth reported having sex after consuming alcohol (20% males and 13.9% females) [ 7 ]. Numerous research studies have established that bars, including taverns, restaurants and shebeens are places where heavy alcohol consumption takes place along with associated HIV sexual risk behaviors [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%